The challenge of neuropsychological assessment of visual/visuo-spatial memory: A critical, historical review, and lessons for the present and future - Diaz-Orueta, Unai; Rogers, Bronagh M.; Blanco-Campal, Alberto; Burke, Teresa (Frontiers in Psychology, 2022)
A proliferation of tests exists for the assessment of auditory-verbal memory processes (see, for example, Lezak et al, 2012). However, from a clinical practice perspective, the situation is less clear when it comes to the ready availability of reliable and valid tests for the evaluation of visual/visuo-spatial memory processes. Whilst, at face value, there appear to be a wide range of available tests of visual/visuo-spatial memory, utilizing different types of materials and assessment strategies, a number of criticisms have been, and arguably should be, levelled at the majority of these tests. The criticisms that have been directed toward what are typically considered to be visual/visuo-spatial memory tests, such as (1) the potential for verbal mediation, (2) over-abstraction of stimuli, (3) the requirement of a drawing response and (4) the lack of sensitivity to unilateral brain lesions, mean that, in reality, the number of readily available valid tests of visual/visuo-spatial memory is, at best, limited. This article offers a critical, historical review on the existing measures and resources for the neuropsychological assessment of visual/visuo-spatial memory, and it showcases some examples of newer tests that have aimed to overcome the challenges of assessing these important aspects of memory. The article also identifies new trends and examples of how technological advances such as virtual reality may add value to overcome previous obstacles to assessment, thereby offering professionals more reliable, accurate means to evaluate visual/visuo-spatial memory in clinical practice.